2021
DOI: 10.36456/jet.v6.n02.2021.4047
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Video for Distance Learning During Covid-19 Pandemic: Students’ Voice

Abstract: During covid-19 pandemic, teachers need to change the activity from a face-to-face into distance learning activity. There may many methods and media used by the teacher, one of them is video. One of the aims is to assist teachers in explaining the material and attracting students' interest. Hence, this study aims to find out the benefits of the use video in teaching and learning activity in pandemic situation. In this study, the researchers investigated what the benefit of the use of video for English learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Clarity of instructions and balanced use of colors, images and writing can support students to understand concepts to make them more visible. This is in line with the opinion of Utami et al (2021), which states that the use of learning multimedia can motivate students and increase interest in learning. In addition, with the use of multimedia, students can understand lessons easily (Septiani & Rejekiningsih, 2020).…”
Section: Aspects Of Formatsupporting
confidence: 86%
“…Clarity of instructions and balanced use of colors, images and writing can support students to understand concepts to make them more visible. This is in line with the opinion of Utami et al (2021), which states that the use of learning multimedia can motivate students and increase interest in learning. In addition, with the use of multimedia, students can understand lessons easily (Septiani & Rejekiningsih, 2020).…”
Section: Aspects Of Formatsupporting
confidence: 86%
“…19 pandemic, which can help educators to teach difficult materials and materials that require practical activities. The use of learning videos during the COVID-19 pandemic is very important (Wibawa & Muhidin, 2021;Utami et al, 2021). The use of video media is also favoured by students because it can help students learn at home, and motivate students to learn.…”
Section: Ijhsmentioning
confidence: 99%
“…The study by Utami A.R. et al showed the positive potential of using educational videos in learning English as a foreign language, as it helps to increase motivation, learn new vocabulary and improve the pronunciation of English words [8] which can be fully utilized in the modern world, where most people have access to streaming services and video hosting sites such as YouTube, Facebook Shorts, TikTok, Instagram.…”
mentioning
confidence: 99%